A Model of Development for the Digital Competencies in Nursing Students at Boromarajonani College of Nursing Nakhon Phanom, Nakhon Phanom University - Arayasinlapathon, Nadnapa; Somkumlung , Patchanee; Punaglom , Nedruetai (Medical Journal of Sakon Nakhon Hospital, 2024)
This participation action research was conducted to develop a model for the digital competencies in nursing students at Boromarajonani college of nursing Nakhon Phanom, Nakhon Phanom University. The samples were researchers, digital experts, representative teachers, representative health workers and representative students in each year. Ninety-six samples participated in the research project voluntarily. Data were collected by semi-structured interview, focus group discussion, observation, and brainstorming. The qualitative data were analyzed using content analysis. The quantitative data were analyzed using frequency and percentage. The results showed that the developed model for the digital competencies in nursing students at Boromarajonani college of nursing Nakhon Phanom, Nakhon Phanom university was the PDE’s model consisted of 3 elements: 1) Policy 2) Digital competencies and 3) Evaluation.The digital competencies for nursing students consisted of 8 elements: 1) Digital literacy 2) Digital skills 3) Attributes 4) Critical thinking and Problem solving 5) Adaptive and Learning 6) Ethics, Law, and Security 7) Communication & Collaboration and 8) Creative and Innovations. This research suggested that the institutions should manage the digital competencies of nursing students particularly the aspects in which students had less competency than others such as critical thinking and problem solving, ethics, law, and security, and Creative and Innovations.